Hyperpigmentation of hard palate induced by chloroquine therapy - Benevenuto de Andrade, Bruno Augusto; Padrón Alvarado, Nelson Alejandro; Muñoz Campos, Edgar Manuel; De Lima Morais, Thayná Melo; Martínez Pedraza, Ricardo (J Clin Exp Dent, 2017)
Abstract The antimalarials are one of the most commonly prescribed drugs for conditions such as lupus erythematosus and rheumatoid arthritis, and the side effects, though infrequent, are well known. The antimalarial agent chloroquine diphosphate usually causes pigmentary changes in the oral mucosa characterized by a bluish-grey to black discolorations mainly in the hard palate. Considering only the hard palate hyperpigmentation caused by chloroquine, to the best of our knowledge, only 13 cases have been reported in the English language literature. We described an additional case of palate hyperpigmentation related to the chronic use of chloroquine diphosphate in a 60-year-old Mexican woman. Although the diagnosis is usually made based on medication history and clinical presentation, a biopsy specimen may be helpful to confirm the diagnosis. Clinicians must be aware of these drugs and their adverse effects in order to make the correct diagnosis and decide on the optimal treatment for the condition. Key words: Oral cavity, hard palate, hyperpigmentation, chloroquine, antimalarials